TAFSIR HERMENEUTIKA POLITIK ATAS GEJALA DEMOKRASI VERSUS DINASTI PADA PILKADA SERENTAK 2015 - Dewi Masyitha (Dialogia: Islamic Studies and Social Journal, 2015)
Abstract: Regional head and deputy regional head (Election) simultaneously is an important moment trip democracy in Indonesia. ELECTIONS simultaneously are the implications of Law No. 1 Year 2015 about Governor and Deputy Governor Elections, Regent and Vice Regent, Mayor and Deputy Mayor are set by Parliament. However, democracy at the local or regional level has the potential to be capitalistic, emotional and transactional. ELECTION tends to only be a handful of people who have space access powerful in the world of politics, in order to perpetuate its power among them are a political dynasty. It is certainly a threat to democracy. The writer through hermeneutic approach explained that the actual political dynasty in law and legislation, it is not wrong. However, when viewed from the side of political ethics, leadership regeneration, utilization of natural resources, improvement of people's welfare, and opportunities for other people, especially from ordinary citizens, the political dynasty will be unhealthy. Political dynasty tends to be used to perpetuate power and an arena for the accumulation of personal wealth coffers of the state money. Moreover, political dynasty is very potential for a worse bureaucratic accountability. Keywords: Hermeneutika, Demokrasi dan Politik Dinasti